HAK IMAMAH SHALAT BAGI PEREMPUAN (Antara Misi Pembebasan Alquran Dan Belenggu Mazhab Fikih) - Kurdi Fadal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This paper examines the right for women as imam prayer for men in the Quranic and Islamic jurisprudence (school of thouht) perspectives. Based on the mission of Quranic liberation, every man and woman has the right that can not be limited by gender status, because Alquran gives equal rights for each to worship and to be devout to God, including as an imam prayer for men. However, the four schools of fiqh (Hanafian, Malikian, Syafi'ian, and Hanabilan) expressed otherwise. They stated that woman should not to be as an imam prayer of men. Although small fraction of fuqaha permited that action, but the mainstrem of Islamic school of thought is more widely supported by the majority of Muslim community and at a time it shackle them. The shackle is influenced by religious texts positioning women as root of slander. The factor is compounded by the historical fact that the interpretation of religious texts is merely dominated by men.